PEMIKIRAN TASAWUF KH. MOCHJAR DAHRI DALAM KITAB MURSYID AL-‘IBȂD ILȂ SABȊL AR-RASYȂD DAN ȂTSȂR AT-TASHAWWUF FȊ HAYȂT AL-MUSLIM - Alamsyah Alamsyah; Irfan Noor; Dzikri Nirwana (Jurnal Ilmiah Ilmu Ushuluddin, 2021)
Purification movements usually tend to reject outright to Sufism, but KH. Mochjar Dahri as the purifier actually appreciated and accepted Sufism as part of Islamic teaching, although many Sufism teachings did not appropriate in the Qur'an and as-Sunnah which he criticized and renewed. Therefore, it is necessary to be studied deeper on his Sufism thoughts. This research aims to study the sufism thought of KH. Mochjar Dahri in the Mursyid al-‘Ibȃd ilȃ Sabȋl ar-Rasyâd and Ȃtsȃr at-Tashawwuf fȋ Hayȃt alMuslim. This type of research is a study of figure thought. The data are collected through literature and field study. As a result: 1) KH. Mochjar Dahri’s thought related to sufism showed in Mursyid al-‘Ibȃd ilȃ Sabȋl ar-Rasyâd is about al-aqabât which includes taubah, tauhid, dzikir, sabar, syukur, tawakkal, ridhâ, and mahabbah. KH. Mochjar Dahri in his work used the term al-aqabât, whereas Sufi scholars usually use the term al-maqâmât, but the term al-aqabât mentioned above seems to have similarities, even though it has differences in the term of al-maqâm. The Sufism thoughts of KH. Mochjar Dahri in the Ȃtsȃr at-Tashawwuf fȋ Hayât al-Muslim was divided into two typologies of Sufism, namely true Sufism (at-tashawwuf ash-shahîh) and deviant Sufism (at-tashawwuf al-mukhti`). Sufism according to him is the practice of shari’ah physically and mentally on the foundation of the Qur’an and as-Sunnah maximally and optimally. The practice of the Five Pillars of Islam and the Five Pillars of Faith are applied in the form of al-ihsân, which is called Sufism, and 2) The pattern of KH. Mochjar Dahri’s sufism in the Mursyid al-‘Ibȃd ilȃ Sabȋl ar-Rasyâd is akhlâqî/‘amalî. The pattern of KH. Mochjar Dahri’s sufism in the Ȃtsȃr at-Tashawwuf fȋ Hayât al-Muslim is a neo-sufism that emphasizes purity and activist characteristics